Near Infrared Spectroscopy based Soil Nitrogen measurement - A Review (International Journal of Current Engineering and Technology, 2014)
Spectroscopy is a rapid, simple, non-destructive and analytical technique, which has been increasingly used for agricultural and food analysis processes. Soil nitrogen, being an important macronutrient of the soil, measurement of total Nitrogen (TN) content can be used as an index of crop productivity. Near infra-red (NIR) spectroscopy can accurately predict the soil nitrogen content by evaluating reflected Near Infra-red rays intensity. The need of expensive and bulky spectrometers is eliminated by use of light-emitting diode (LED) as a Near Infra-red light source, making the system cost effective and portable. The paper reviews brief study of different technologies used for the purpose and explains in detail the spectroscopy concept. A comparative study between various modern calibration methods has lead to a conclusion that, wavelet analysis can offer utmost accuracy of prediction.
Keywords: Spectroscopy, NIR, Total Nitrogen, Spectrometers, LED, Artificial Neural Networks, wavelet.